HEPATOPROTECTIVE POTENTIAL OF IN VITRO BACOPA MONNIERI L AGAINST CARBON TETRACHLORIDE - INDUCED HEPATOTOXICITY IN ALBINO MICE - TEJOVATHI GUDIPATI; PRATIMA SRIVASTAVA; REKHA BHADAURIA; G.B.K.S. PRASAD (International Journal of Pharma and Bio Sciences, 2012)
Bacopa monnieri L plants raised through micropropagation were evaluated for the production of major secondary metabolite, ‘Bacoside-A’ and its pharmacological properties in comparison to the conventional source i.e. , natural ( in vivo) plants. The hepatoprotective function of the ethanolic extract containing Bacoside-A of in vitro grown B. mannieri was evaluated in carbon tetrachloride (CCl4) - intoxicated albino mice. Analysis of ethanolic extract of in vitro raised Bacopa plants by HPTLC confirmed presence of Bacoside-A identical to that of seed borne Bacopa. Administration of Bacopa ethanolic extract from either source (in vitro or natural) markedly prevented CCl4-induced hepatic damage in albino mice model as indicated by the levels of serum markers (SGPT, SGOT and Bilirubin) of hepatic damage. The present study confirmed that in vitro generated Bacopa monnieri produces ‘Bacoside-A’ with pharmacological function identical to that generated from natural plantlet. Thus, in vitro Bacopa cultures serve as efficient alternate source of ‘Bacoside-A’ for pharmacological use.